A comprehensive description of the TolC effect on the antimicrobial susceptibility profile in Enterobacter bugandensis - Li, Bingyu; Zhang, Ji; Li, Xiaodong (Frontiers in Cellular and Infection Microbiology, 2022)
Enterobacter bugandensis is an emerging human pathogen in which multidrug resistant strains have been continuously isolated from various environments. Thus, this organism possesses the potential to pose challenges in human healthcare. However, the mechanisms, especially the efflux pumps, responsible for the multidrug resistance in E. bugandensis remain to be well elucidated. Here, we reclassified an Enterobacter strain, CMCC(B) 45301, from species cloacae to bugandensis, on the basis of its whole genome sequence. With the genomic reference, we identified the specific CMCC(B) 45301 homologues of the TolC dependent efflux-pump genes characterized in Escherichia coli, and subsequently constructed the tolC deletion mutant in CMCC(B) 45301. The tolC mutant and the wild type were subjected to susceptibility tests using 26 different antimicrobial agents. Our results revealed that lacking tolC causes 4- to 256-fold decrease in the minimal inhibitory concentrations of piperacillin, gentamicin, kanamycin, tetracycline, norfloxacin, ciprofloxacin, chloramphenicol, and erythromycin against CMCC(B) 45301. In addition, the inhibition zones formed by cefuroxime, cefoperazone, amikacin, streptomycin, minocycline, doxycycline, levofloxacin, florfenicol, trimethoprim-sulfamethoxazole, azithromycin, lincomycin, and clindamycin for the tolC mutant were larger or more obvious than that for the parent. These data suggested the important role played by TolC in CMCC(B) 45301 susceptibility to common antibiotic families covering ß-lactam, aminoglycoside, tetracycline, fluoroquinolone, phenicol, folate pathway antagonist, macrolide, and lincosamide. Deletion for tolC also increased the susceptibility of CMCC(B) 45301 to berberine hydrochloride and the Bacillus crude extract (BCE), two natural product-based agents. Finally, we assayed the synergistic effects combining BCE and other TolC-affected compounds, and found that erythromycin, norfloxacin, and ciprofloxacin can potentiate the antibacterial activity of BCE against CMCC(B) 45301. This study elaborated the comprehensive TolC effect on the antimicrobial susceptibility profile in E. bugandensis, which might contribute to the development of more therapeutic options against this nosocomial pathogen.